ANALISIS PENGGUNAAN MEDIA PEMBELAJARAN LKS OLEH GURU DALAM PROSES PEMBELAJARAN SOSIOLOGI PADA SISWA KELAS XII IIS SMA NEGERI 2 SINGKAWANG - Mariati Mariati; Rustiyarso Rustiyarso; Riama Al Hidayah (Jurnal Pendidikan dan Pembelajaran Khatulistiwa (JPPK), 2021)
Abstract This study aims to find out the students' learning activeness in the use of LKS media in the learning process. Besides, to increase the motivation of teachers' and to know the students' learning outcomes by using LKS learning media in the process of learning sociology subjects in grade XII IIS. This research uses qualitative research method with descriptive method. Data sources in this study are divided into 2 data sources, namely primary data sources and secondary data sources, primary data sources are teachers and students, secondary data sources are data taken from literature and documents in schools. For the data collection techniques used are observation, documentation, and in-depth interviews. The results of this study show that in this pandemic, the use of LKS media to be applied to the teaching and learning process online. Because LKS is considered quite effective because the content of the LKS itself is a summary of the material that has included all the brief and clear understandings. With the use of LKS media, participants are more active and can be motivated to learn independently. And do not forget the role of teachers and parents to participate in helping to build the motivation of learners to be able to maintain the spirit of learning even though learning online. Keywords : Learning Process, Student Worksheets (LKS), Use Of Learning Media